Complicaciones de la cirrosis hepática en los pacientes hospitalizados en el área de clínica del Hospital Isidro Ayora de la ciudad de Loja - Castillo Caamaño, Paola Fernanda (2016)
Hepatic cirrhosis is the result of a disease which has damaged the liver leading to the decrease of the hepatic parenchyma with a formation of fibrosis, regenerative nodules and changes in the circulation. This research project has as objectives: identifying the most frequent complication which is cause of hospitalization in patients with hepatic cirrhosis; determining the frequency of the complications by gender, and know the relationship between the beginning of cirrhosis and the age of appearance of the complication. A descriptive, retrospective and transversal applied type study was undertaken to 61 patients with the diagnosis of hepatic cirrhosis who were hospitalized in the clinical area of Isidro Ayora Hospital from the city of Loja, in the period between November 2014 to November 2015; the epicrisis of the clinical records was used as the source of information, the same one that was registered in a data collection form. The following outcomes were obtained: the major complications of hepatic cirrhosis which were reason for hospitalization are, upper gastrointestinal bleeding (60.7%), ascites (27.9%), hepatic encephalopathy (13.1%); in relation to gender it was presented in men (60.7%) and women (39.3%); the hepatic cirrhosis is more frequent between 70-79 years (24.6%); the time of appearance of the complications it is presented mostly in patients diagnosed as having cirrhosis less than 1 year (44.3%). Of the present research work it can be concluded that: The leading complication which was reason for hospitalization in the patients with hepatic cirrhosis was the upper gastrointestinal bleeding. Keywords: Hepatic cirrhosis, complications, upper gastrointestinal bleeding.